2.39. Rozwiąż równania: a) x-3)(x+2)+(5-x)(x+1)=0 2x+1)(x-4)=2(1-x)(5-x) c) 4x – (x + 5)(x – 7) = x(1 – x) b) d) (x – 2)(4 + x) = (x + 3)(x – 1) e) 2 + (2x – 3)(x + 1) = 3x – 2(5 – x ^ 2) f) 4(x + 5) – 0, 5(x – 3) * (6 – 2x) = x ^ 2 + 1 1 – (2x – 1)(x + 3) + 5(x + 0, 8) = 0 g) h) (x – 2)(x – 5) + 1 3/4 = x – (32x – 56)/4

2.39. Rozwiąż równania: a) x-3)(x+2)+(5-x)(x+1)=0 2x+1)(x-4)=2(1-x)(5-x) c) 4x – (x + 5)(x – 7) = x(1 – x) b) d) (x – 2)(4 + x) = (x + 3)(x – 1) e) 2 + (2x – 3)(x + 1) = 3x – 2(5 – x ^ 2) f) 4(x + 5) – 0, 5(x – 3) * (6 – 2x) = x ^ 2 + 1 1 – (2x – 1)(x + 3) + 5(x + 0, 8) = 0 g) h) (x – 2)(x – 5) + 1 3/4 = x – (32x – 56)/4